2017
DOI: 10.1111/jfb.13463
|View full text |Cite
|
Sign up to set email alerts
|

Marine depth use of sea trout Salmo trutta in fjord areas of central Norway

Abstract: The vertical behaviour of 44 veteran sea trout Salmo trutta (275-580 mm) in different marine fjord habitats (estuary, pelagic, near shore with and without steep cliffs) was documented during May-February by acoustic telemetry. The swimming depth of S. trutta was influenced by habitat, time of day (day v. night), season, seawater temperature and the body length at the time of tagging. Mean swimming depth during May-September was 1·7 m (individual means ranged from 0·4 to 6·4 m). Hence, S. trutta were generally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 29 publications
4
24
0
Order By: Relevance
“…Trout from streams with low water level during winter may migrate to a neighbouring watercourse for overwintering (Aldvén & Davidsen, 2017) or stay in marine waters (Eldøy et al, 2017;Olsen et al, 2006). Trout from streams with low water level during winter may migrate to a neighbouring watercourse for overwintering (Aldvén & Davidsen, 2017) or stay in marine waters (Eldøy et al, 2017;Olsen et al, 2006).…”
Section: Migration Can Improve Survivalmentioning
confidence: 99%
See 2 more Smart Citations
“…Trout from streams with low water level during winter may migrate to a neighbouring watercourse for overwintering (Aldvén & Davidsen, 2017) or stay in marine waters (Eldøy et al, 2017;Olsen et al, 2006). Trout from streams with low water level during winter may migrate to a neighbouring watercourse for overwintering (Aldvén & Davidsen, 2017) or stay in marine waters (Eldøy et al, 2017;Olsen et al, 2006).…”
Section: Migration Can Improve Survivalmentioning
confidence: 99%
“…In northern Europe, immature trout can also return to freshwater in summer after a short stay at sea. Ionoregulation in sea water at low temperature is arduous, but anadromous trout have been observed at sea during winter and tolerate full salinity seawater at temperatures as low as 1-2°C (Eldøy et al, 2017;Knudsen et al, 2009;Olsen, Knutsen, Simonsen, Jonsson, & Knutsen, 2006). In the brackish Baltic Sea, parr can migrate from freshwater to the Baltic coastal zone without undergoing smolting.…”
Section: Phenotypic Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, low biodiversity has been observed at sampling stations in Zone 2, close to the border between Zone 1 and 2, indicating a reduced selection of prey for sea trout in this habitat (Kroglund, Dahl, & Oug, 1998). Salmonids have shown great differences in movement rates contrasting day and night (Alanärä, Burns, & Metcalfe, 2001;Candy & Quinn, 1999;Eldøy et al, 2017;Goetz, Baker, Buehrens, & Quinn, 2013), and it has been shown for steelhead trout (Oncorhynchus mykiss) that horizontal movement rates increase twofold during daylight compared to night in the marine habitat (Ruggerone, Quinn, Mcgregor, & Wilkinson, 1990). There were significantly more excursions from the reserve during day than night, implying greater horizontal movement during day.…”
Section: Re Sultsmentioning
confidence: 99%
“…As a result of its cultural and economic importance, considerable previous research has focused on the challenges facing S. salar populations (Limburg & Waldman, 2009). In contrast, considerably less attention has been given to the causes of decline of S. trutta (Drenner et al, 2012;Eldøy et al, 2017;Glover et al, 2017).…”
Section: Introductionmentioning
confidence: 99%